Association of inter-arm systolic blood pressure differences with arteriosclerosis and atherosclerosis: A cohort study of 117, 407 people. (February 2022) - Lee, Seung-Jae; Kim, Hyunah; Oh, Byeong Kil; Choi, Hyo-In; Lee, Jong Young; Lee, Sung Ho; Kim, Byung Jin; Kim, Bum Soo; Kang, Jin Ho; Kang, Jeonggyu; Kim, Seong Hwan; Sung, Ki-Chul
Abstract: Background and aims: Inter-arm blood pressure differences (IADs) are known to be associated with adverse cardiovascular outcomes. We evaluated the distribution of IADs in a large cohort of apparently healthy people and the association of IADs with brachial-ankle pulse wave velocity (baPWV) and coronary artery calcium (CAC). Methods: Blood pressure was measured in both arms of 117, 407 people who participated in the Kangbuk Samsung Health Study. IAD was defined as the absolute difference in systolic blood pressure in both arms and was confirmed by measuring the baPWV using an automatic oscillometric device. Arterial stiffness was measured by the baPWV, and CAC was assessed using multi-detector computed tomography. Results: The mean IAD in the overall subjects was 3.09 ± 2.83 mmHg, 6 mmHg in the 90th percentile, 8 mmHg in the 95th percentile, and 10 mmHg in the 97th percentile. In the multivariable-adjusted analysis of 92, 949 subjects excluding those with a history of HTN, DM, and cardiovascular disease (CVD), increasing IAD did not statistically increase the risk of developing a CAC >0. However, IAD was associated with a baPWV >1400 cm/s (odds ratio [95% confidence interval], 1.23 [1.13–1.35] in the total cohort, 1.19 [1.08–1.31] in males, and 1.39 [1.11–1.73] in females). Conclusions: More than 97% of all participants had an IAD of 10 mmHg or less. IAD was significantly associated with arterial stiffness, reflecting arteriosclerosis, but not with the presence of CAC, reflecting atherosclerosis. IAD may be a valuable tool for the early detection of asymptomatic, low-risk individuals with subclinical arterial disease. Graphical abstract: Image 1 Highlights: More than 97% of the total population had an IAD of 10 mmHg or less. Increased IAD were positively correlated with brachial-ankle pulse wave velocity. Even if the IAD is less than 10 mmHg, arteriosclerosis if not atherosclerosis, may already be in progress. In primary care, IAD may be a useful tool to identify people with subclinical arterial diseases with normal values for traditional risk factors.